2012
DOI: 10.1159/000345124
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic Evidence of Health Effects from Long-Distance Transit of Chemical Weapons Fallout from Bombing Early in the 1991 Persian Gulf War

Abstract: Background: Military intelligence data published in a companion paper explain how chemical fallout from US and Coalition bombing of Iraqi chemical weapons facilities early in the air campaign transited long distance, triggering nerve agent alarms and exposing US troops. We report the findings of a population-based survey designed to test competing hypotheses on the impact on chronic Gulf War illness of nerve agent from early-war bombing versus post-war demolition. Methods: The US Military Health Survey perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 71 publications
0
47
0
Order By: Relevance
“…A weakness of this study is the use of the Khamisiyah plume model for exposure assessment. Although several studies have used the plume model to determine exposure [40-42], a report published by the General Accountability Office in 2004 concluded that the Department of Defense/Central Intelligence Agency 2000 Khamisiyah plume model was unsupported and recommended that Department of Defense and Department of Veteran Affairs no longer use this plume model for epidemiological studies of the Gulf War [43]. The Department of Veteran Affairs concurred with this decision but allowed for completion of studies already underway, including the work presented here.…”
Section: Discussionmentioning
confidence: 99%
“…A weakness of this study is the use of the Khamisiyah plume model for exposure assessment. Although several studies have used the plume model to determine exposure [40-42], a report published by the General Accountability Office in 2004 concluded that the Department of Defense/Central Intelligence Agency 2000 Khamisiyah plume model was unsupported and recommended that Department of Defense and Department of Veteran Affairs no longer use this plume model for epidemiological studies of the Gulf War [43]. The Department of Veteran Affairs concurred with this decision but allowed for completion of studies already underway, including the work presented here.…”
Section: Discussionmentioning
confidence: 99%
“…Survivors of the sarin attack in the Tokyo subway suffered chronic deficits including impaired psychomotor functions such as finger tapping, a tendency towards worse performance on the Benton visual memory retention test, and smaller than normal brain volumes in the hippocampus and other brain regions compared to unexposed controls [1,2]. Similarly, exposure to sarin from the demolition of depositories containing sarin during the bombing phase of the 1991 Gulf War and after the ground war is a suggested cause of the neuropsychological disabilities suffered by 30 % or more of the veterans [3]. It should be noted that, despite this apparent link between sarin exposure and cognitive impairment, a second school of thought purports that these deficits may be linked to the emotional response to the trauma of exposure or warfare and are more consistent with the symptoms of post-traumatic stress disorder [see [4] for review].…”
Section: Introductionmentioning
confidence: 99%
“…Persian Gulf soldiers were exposed to multiple anticholinesterases during their deployment. Exposures derived, not only as self-applied insecticides (i.e., chlorpyrifos) and nerve gas prophylactics (PB) but also from the intentional and/or accidental release of nerve agents (Sarin) and other carbamates or organophosphates with which they had voluntary and/or involuntary contact (Fricker et al, 2000;Haley et al, 2012;see Binns et al, 2008). Chronic exposure to varied cholinesterase inhibitors might alter the physiology of cholinergic receptors and their downstream targets (K v 7).…”
Section: Discussionmentioning
confidence: 99%